Ibrahim Muminov’s Scientific and Philosophical Heritage and Subjective Approaches to His Scientific Activity under the Rule of the Former Ideology - Ibodova Nasiba Komilovna (International Journal on Integrated Education, 2022)
The article presents the views and analysis of the scientific and philosophical heritage of academician Ibrahim Muminov and the subjective approaches to the scientific activity of the scientist during the reign of the former dictatorial ideology.